Cross-CRP Analysis of Partnership Strategies in the 2017-2022 CRP2 - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2017)
This brief provides a summary analysis of how well the CGIAR Research Programs (CRPs) are planning the design and implementation of their partnership strategies, and how the strategic partnership activities contribute to the outputs and outcomes of the CRPs.